Characterization of endophytic bacteria in Vietnamese rice seeds - Mai, Thi Phuong Nga; Nguyen, Phuong Van (Academia Journal of Biology, 2024)
Rice is a staple food and is commonly used in daily life not only in Vietnam but worldwide. However, pests, diseases, and nutrient deficiencies are threatening Vietnam’s rice production by causing significant damage. The endophytic bacteria (EB) which are isolated from plants, may help improve certain quality traits of rice seeds assist plants in coping with abiotic and biotic stresses from the environment. Therefore, this study aims to investigate some promising characteristics of EBs in rice seeds, including gelatinase production, starch hydrolysis, phosphate solubilizing, cellulase, and IAA synthesis. Rice seeds from various rice varieties were used to isolate the endophytic bacteria. The bacteria were grown in Petri dishes or glass test tubes in some selective media in a controlled environment to screen for investigated traits. A total of five EBs were isolated, and MALDI-TOF mass spectrometry with a log score of MALDI Biotypes greater than 2.0 was employed for bacterial identification. Interestingly, the results revealed that the bacteria in rice grains have a high ability to synthesize cellulase, hydrolyze starch and gelatin, and produce auxin. The highest cellulase activity was associated with Staphylococcus caprae while Micrococcus luteus exhibited maximum IAA hormon and gelatinase enzyme production. Starch hydrolysis was highest in Bacillus. However, these bacteria showed low phosphate solubilization ability. The promising bacteria identified in this study include Bacillus cereus, M. luteus, and Bacillus atrophaeus. The promising results from our study can be utilized for further in vivo studies in rice plants to develop biocontrol reagents and biofertilizers for agricultural applications.